Erratum to "Bispecific Antibody-Bound T Cells as a Novel Anticancer Immunotherapy" [Biomol. Ther. 30 (2022) 418-426, 10.4062/biomolther.2022.015] - Cho, Jaewon; Tae, Nara; Ahn, Jae Hee; Chang, Sun Young; Ko, Hyun Jeong; Kim, Dae Hee (Biomolecules and Therapeutics, 2024)
The authors request the correction of the annotation in Fig. 3B and 3D on page 422, as well as in Fig. 4C on page 423. Due to the modification of the annotation in Fig. 3B and 3D, several sentences will also need to be adjusted accordingly. In figure legend 3A and 3D on page 422, BiTE (2 μg/kg) should change to BiTE (2 mg/kg). (Figure presented) In result section subtitle ‘Tumor growth was suppressed after transferring BiTE-bound polyclonal CD8 T cells’, the sentence of ‘Introduced mCD3xPD-L1 BiTE:T cells significantly suppressed tumor growth compared to both 2 μg/kg of BiTE intraperitoneal injection and plain T cell treatment (Fig. 3B)’ need to be changed as ‘Introduced mCD3xPD-L1 BiTE:T cells significantly suppressed tumor growth compared to both 2 mg/kg of BiTE intraperitoneal injection and plain T cell treatment (Fig. 3B)’. The annotation in Fig. 4C has been revised: the colors of CTL CAR-T and ML39 CAR-T have been altered. CTL CAR-T is now depicted in white, while ML39 CAR-T is represented in red. (Figure presented) During the preparation of the manuscript and figures, the authors inadvertently made a typographical error. This error does not impact the conclusions of the article. Nonetheless, the authors sincerely apologize for any inconvenience caused by this oversight.